Building a new, better normal after COVID-19. Issue 6 (June 2021) - Blake, Nancy
Abstract : During the past year, frontline nurses have devised novel ideas to deal with the realities of the COVID-19 pandemic. Discover ways to keep these improvements going beyond the pandemic through the lens of healthy work environment standards.